Additive cardiotoxicity of a bisphenol mixture in zebrafish embryos: The involvement of calcium channel and pump - Salim Arrokhman; Yueh-Hsia Luo; Pinpin Lin (Ecotoxicology and Environmental Safety, 2023)
Bisphenol A (BPA) and its analogs, such as bisphenol F (BPF), bisphenol AF (BPAF), and bisphenol B (BPB), are often simultaneously detected in environmental and human specimens. Thus, assessing the toxicity of bisphenol (BP) mixtures is more relevant than assessing that of each BP type. Here, we found that BPs, individually or in a mixture, concentration-dependently and additively increased the mortality of zebrafish embryos (ZFEs) at 96 h post fertilization (hpf) and induced bradycardia (i.e., reduced heart rate) at 48 hpf, indicating their cardiotoxic potency. BPAF was the most potent, followed by BPB, BPA, and BPF. We then explored the mechanism underlying BP-induced bradycardia in ZFEs. Although BPs increased the mRNA expression of the estrogen-responsive gene, treatment with the estrogen receptor inhibitor ICI 182780 did not prevent BP-induced bradycardia. Because they did not change cardiomyocyte counts or heart development–related gene expression, BPs might not affect cardiomyocyte development. By contrast, BPs might impair calcium homeostasis during cardiac contraction and relaxation through the downregulation of the expression of the mRNAs for the pore-forming subunit of L-type Ca2+ channel (LTCC; cacna1c) and sarco/endoplasmic reticulum Ca2+-ATPase (SERCA; atp2a2a). BPs reduced SERCA activity significantly. BPs also potentiated the cardiotoxicity induced by the LTCC blocker nisoldipine, conceivably by inhibiting SERCA activity. In conclusion, BPs additively induced bradycardia in ZFEs, possibly by impeding calcium homeostasis during cardiac contraction and relaxation. BPs also potentiated the cardiotoxicity of calcium channel blockers.